Importance of volatile–char interactions during the pyrolysis and gasification of low-rank fuels – A review - Li, Chun-Zhu (Elsevier Ltd, 2013)
Volatile–char interactions are an important phenomenon in almost all existing gasification processes. The volatile–char interactions can very significantly affect almost every aspect of low-rank fuel gasification, including the volatilisation of alkali and alkaline earth metallic species that are inherent catalysts for gasification, the evolution of char structure, the dispersion of inherent catalysts and thus the reactivity of char. The volatile–char interactions can also influence the formation of pollutant-forming species such as NH3. This paper provides an overview of our recent work in this area. The essence of volatile–char interactions appears to be the interactions between radicals, especially H radicals, and the char during pyrolysis and gasification. The volatile–char interactions must be an important consideration in the development of new gasification technologies for low-rank fuels such as brown coal and biomass to minimise the adverse effects and maximise the positive effects of volatile–char interactions during the gasification of low-rank fuels.